1986
DOI: 10.1177/030098588602300613
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Tumors in a Colony of Beagle Dogs

Abstract: In a lifetime study, female beagle dogs in a closed colony were administered 226radium and 90strontium. An unirradiated control group was included in the study. A total of 223 of 356 dogs at risk developed 1,112 mammary proliferative growths (hyperplastic nodules and neoplasms). There was no correlation between occurrence and types of lesions in radiation and control groups. The age range for first occurrence of lesions was 10.4 to 13.9 years; hyperplastic nodule and benign mixed tumor occurred 1 to 2 years ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…Growing age is highly related with malignancy due to accumulation of tumourogenous factors leading to malignant tumours by advancing age (Zatloukal et al 2005). Tumour development was most commonly determined in inguinal mammary glands which is in accordance with previous studies (Mulligan 1975, Moulton et al 1986, Moulton 1990, Miller et al 2001, Vural and Aydın 2001. The reason of the increased frequency in the last two glands is unknown, however, several explanations such as presence of larger mass of tissue, or greater proliferative change in response to oestrogen in the most caudal glands have been suggested (Moulton et al 1986, Moulton 1990).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Growing age is highly related with malignancy due to accumulation of tumourogenous factors leading to malignant tumours by advancing age (Zatloukal et al 2005). Tumour development was most commonly determined in inguinal mammary glands which is in accordance with previous studies (Mulligan 1975, Moulton et al 1986, Moulton 1990, Miller et al 2001, Vural and Aydın 2001. The reason of the increased frequency in the last two glands is unknown, however, several explanations such as presence of larger mass of tissue, or greater proliferative change in response to oestrogen in the most caudal glands have been suggested (Moulton et al 1986, Moulton 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The reason of the increased frequency in the last two glands is unknown, however, several explanations such as presence of larger mass of tissue, or greater proliferative change in response to oestrogen in the most caudal glands have been suggested (Moulton et al 1986, Moulton 1990). Furthermore, hyperplastic nodules which occur most commonly in the last two glands, are considered the beginning stages of tumourogenesis (Moulton et al 1986, Hellmen 1996.…”
Section: Discussionmentioning
confidence: 99%
“…22 The age of onset, however, may vary depending on the natural life span of the breed of dog, and most authors report an average age range of 8-11 years, indicating that this is a malignancy of the middle-aged or older dog. 10,38,41,69,83,85 Younger dogs are more likely to have benign tumors than older dogs, 35,51,54,92 and a recent study reported a significant difference in age: a mean age of 8.5 years in dogs with benign tumors versus 9.5 years in dogs with malignant tumors. 88 Mammary tumors are rare in dogs under 5 years of age, unless the dogs have been treated with exogenous hormones (progestins).…”
Section: Agementioning
confidence: 98%
“…5,6,54,92 The 2 caudal pairs of glands are most commonly affected, and the axillary mammary glands are often not involved as a first occurrence. 5,6,35,54,92 Mammary tumors are relatively easy to detect on clinical exam and typically appear as 1 or more discrete masses in the glands. The specific clinical findings depend on the biological behavior of the tumor and at what stage of disease they are brought in for veterinary care: Tumors can be small or large, fixed or freely movable, ulcerated, and single or multiple.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…[1][2][3][4][5][6]. Mammary tumors constitute about half of all tumors in female dogs and approximately half of the canine mammary tumors (CMT) are malignant (7,8).…”
Section: Introductionmentioning
confidence: 99%